2021
DOI: 10.3390/vaccines9080892
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of COVID-19 Vaccine Intention among the Saudi Arabian Population: A Cross-Sectional Survey

Abstract: The long-term solution to managing the current COVID-19 pandemic is through mass immunization of the population. However, uncertainty or unwillingness to receive the vaccine could be a barrier in attaining sufficient vaccine coverage. Therefore, understanding the psychology of the population towards the vaccines against COVID-19 is of paramount importance. Our study was aimed at determining the predictors of COVID-19 vaccine intention in the Saudi Arabian population. A structured questionnaire guided by the ‘R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 27 publications
2
20
0
Order By: Relevance
“…Recent studies found that—in the UK and Denmark—the intentions and attitudes toward COVID-19 vaccines did not change despite the negative news surrounding AstraZeneca ( 17 , 18 ). Simultaneously, different studies show a decrease in vaccine acceptance, either directly through surveys in Saudi Arabia ( 19 ) or indirectly through reduced turnout for scheduled vaccinations in Ecuador (although the exact reason for not showing for the vaccinations remains unclear) ( 20 ).…”
Section: Factors That Influence Vaccine Acceptance In the Covid-19 Eramentioning
confidence: 99%
“…Recent studies found that—in the UK and Denmark—the intentions and attitudes toward COVID-19 vaccines did not change despite the negative news surrounding AstraZeneca ( 17 , 18 ). Simultaneously, different studies show a decrease in vaccine acceptance, either directly through surveys in Saudi Arabia ( 19 ) or indirectly through reduced turnout for scheduled vaccinations in Ecuador (although the exact reason for not showing for the vaccinations remains unclear) ( 20 ).…”
Section: Factors That Influence Vaccine Acceptance In the Covid-19 Eramentioning
confidence: 99%
“…As of 17 September 2021, it was estimated that approximately 50% of the general population in Saudi Arabia was fully vaccinated against COVID-19 [70]. Studies have also been performed to identify the predictors of COVID-19 vaccination in Saudi Arabia [71][72][73]. These studies can be helpful in formulating an intervention to educate the public and reduce misconceptions and accelerate the vaccination coverage of the population [73].…”
Section: Introductionmentioning
confidence: 99%
“…The sociodemographic factors that are correlated with vaccine hesitancy have been explored in some studies in the region [ 28 ]. Still, most have focused on a single country [ 25 ], while other studies did not address these factors [ 24 , 29 ]. This study aims to explore those factors across different countries in the region.…”
Section: Discussionmentioning
confidence: 99%